Pelatihan Karawitan di Paguyuban Laras Budoyo Makmur Desa Sukomakmur, Kajoran, Magelang - Supeno, M. Yoga; Wijaya, Adi (Institut Seni Indonesia Yogyakarta, 2025)
Artikel ini mengkaji implementasi program penyuluhan seni karawitan di Paguyuban